Buffalo: Mediterranean Region - Borghese, A. (Reference Module in Food Science, 2016)
The buffaloes reared in the Mediterranean region are the Asian buffalo or water buffalo, that is, Bubalus bubalis. This species includes two types: (1) the river type, with 50 chromosomes, with an adult male weighing between 450 and 1000 kg and with an annual milk production of 1000–3000 kg; and (2) the swamp type, with 48 chromosomes, with an adult male weighing between 325 and 450 kg and with an annual milk production of up to 600 kg. The river buffalo is reared mainly for milk, whereas the swamp buffalo is reared mainly for draught. Only 3% of the world buffalo population is reared in the Mediterranean region. Significant numbers of buffaloes are at present found only in Italy, Romania, Egypt, Turkey, Azerbaijan, Iraq and Iran. In all these countries, buffaloes represent only a very small portion of total livestock, except in Egypt, where buffaloes are more numerous than cattle. Because of the strong market demand for buffalo cheese, the number of buffaloes has increased in Italy and there is a preference for buffalo dairy products compared to cows' milk products in a few countries. Major morphological differences between the buffalo populations of different countries include (1) the variable size, ranging between a minimum of 280 and 300 kg liveweight for adult females and males, respectively, in Egypt to a maximum of 900 and 1000 kg in Iraq, the most frequent weights being 600 and 800 kg; (2) the shape of the horns; and (3) the coat color, from dark gray and dark brown to black, showing white spots in some cases.